Prevalence of iron, folate, and vitamin B12 deficiencies in 20 to 49 years old women: Ensanut 2012 - Teresa Shamah-Levy; Salvador Villalpando; Fabiola Mejía-Rodríguez; Lucía Cuevas-Nasu; Elsa Berenice Gaona-Pineda; Eduardo Rangel-Baltazar; Norma Zambrano-Mujica (Instituto Nacional de Salud Pública, 2015)
Objective. To describe the prevalence of iron, folate, and B12 deficiencies in Mexican women of reproductive age from the National Health and Nutrition Survey (Ensanut) 2012.Materials and methods. Data came from a  ationalprobabilistic survey, representative from rural and urban areas,and different age groups. Blood samples were obtained from 4 263, 20 to 49 years old women for serum ferritin, vitamin B12 and serum folate oncentrations. The prevalence of deficiencies, was assessed using adjusted logistic regression models. Results. The deficiency of folate was 1.9% (95%CI1.3-2.8), B12 deficiency was 8.5% (95%CI 6.7-10.1) and iron deficiency was 29.4% (95%CI 26.5-32.2). No differences were found when compared with 2006, 24.8% (95%CI 22.3-27.2).Conclusions. The vitamin B12 deficiency is still a problem for women of reproductive age and their offspring in Mexico,while folate deficiency disappeared as a problem. Iron deficiency needs prevention and fortification strategies.